Cover Feature: Direct Access to N‐Unprotected α‐ and/or β‐Tetrasubstituted Amino Acid Esters via Direct Catalytic Mannich‐Type Reactions Using N‐Unprotected Trifluoromethyl Ketimines (Chem. Eur. J. 67/2017). Issue 67 (2nd October 2017) - Sawa, Masanao; Morisaki, Kazuhiro; Kondo, Yuta; Morimoto, Hiroyuki; Ohshima, Takashi
Abstract : A new wind blowing : The use of N ‐unprotected trifluoromethyl ketimines as effective electrophiles in direct catalytic Mannich‐type reactions is reported, giving direct access to N ‐unprotected α‐ and/or β‐tetrasubstituted amino acid esters under proton‐transfer conditions. The first stereoselective construction of vicinal tetrasubstituted carbon stereocenters with N ‐unprotected ketimines is also presented. More information can be found in the Full Paper by H. Morimoto and T. Ohshima et al. onpage 17022 .